Post-traumatic stress disorder. Issue 9 (September 2013) - Wright, Joy; Robinson, Ben
Post-traumatic stress disorder (PTSD) is common in primary care but studies have shown poor levels of knowledge about it among GPs. Diagnosis is often delayed, contributing to high levels of complications such as depression or alcohol misuse. There is good evidence that treatment with trauma-specific psychological therapies can be effective. Prompt diagnosis allows appropriate and timely treatment.